Suplementasi Vitamin E pada Level Nutrien Ransum Berbeda untuk Meningkatkan Pertumbuhan dan Mengatasi Cekaman Panas pada Ayam Lokal IPB-D3: Supplementation of vitamin E in the diet containing different nutrition levels to increase growth and overcome heat stress of local chicken IPB-D3 - Nailis Salsabila; S Sumiati; T Suryati (Jurnal Ilmu Nutrisi dan Teknologi Pakan (Nutrition and Feed Technology Journal), 2022)
This study aimed to evaluate the effect of vitamin E supplementation at different levels of ration nutrition on the variables. 160 IPB-D3 chickens were reared from grower to finisher with 16 experimental units. The experimental design used factorial RAL (2x2) with 4 replications. The first factor was the type of ration namely control rations with nutrient requirements equal to SNI and rations with nutrient requirements more than 10% of SNI (treatment rations) and the second factor was without and with vitamin E supplements 200 ppm vitamin E supplementation. Data were analyzed using ANOVA and Duncan's follow-up test. The variables used included performance, lymphoid organs, blood profile, MDA, and catalase. The results showed that the treatment did not have significant effect on performance, but rations with nutrient content >10% SNI were able to increase body weight gain of IPB-D3 chickens compared to other treatments. The type of ration had a significant effect (p<0.05) on the thymus organ.Vitamin E supplementation was able to increase hemoglobin and basophil levels (p<0.05). There was an interaction between the type of ration and vitamin E supplementation on MDA and catalase (p<0.05). Provision of rations with the nutrient content >10% SNI increased catalase activity. Vitamin E supplementation suppressed the formation of MDA in rations with nutrient content >10% SNI. It can be concluded that supplementation of vitamin E 200 ppm with different rations still maintained lymphoid organs and blood profiles in normal conditions, suppressed MDA formation and increased the antioxidant enzyme activity. Key words: growth, lokal chicken IPB-D3, heat stress, vitamin E